Membangun Peran Serta Hubungan Industrial PT. Karya Cahya Anue Dengan Para Pegawai Untuk Mencapai Tujuan Yang Sama - Resya Dwi Marselina; Didah Nurhidayah; Muhamad Alamsyah Nasution (Pusat Riset dan Inovasi Nasional, 2024)
A company is an aciion carried out by one or more people to achieve the same goal. In other words, a conipany 3 aform of business entity that places greater eniphasis on profit or profit front the goods or Services offered to someone by the conipany. According to DrsUncolin Arsyad, M.Sc, a conipany is a profit-oriented organization that buys input s and input Services and selis goods and Services. A conipany is anyform of business t hal carries out any type of bus iness that is permanent and continuous and/or which is established with f/ie aim of obtaining profit or proflts. Various jields in the conipany must be ahosen aarefullyand thoroughly, becanse there are manyfields in the conipany, induding companies that run their business in the advertising sector. The niethod used in writing this article is a gualitative niethod. Qualitative research is research that looks at the perspective ofsocial reality, naniely by seeing the world as it is, therefbre a qualitative researcher must be someone with an operi mind. Basically, qualitative research has two ohjectives, naniely: first, describing and revealing and second, describing and ezplaining. Based on the results of interviews conducted with HRD PT. Karya Cahaya Anue on November 29 2023. In the interview we asked several questions regarding industrial relations problems at PT. PT. Cahaya Anue’s work includes